Strengthening the Role of Complementary Medicine to Address Health Workforce Shortages in Primary Health Care in Asia: AASSA-PAS Regional Workshop Recommendations - Tasleem Akhtar; Zabta K. Shinwari (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2019)
According to the World Health Organization (WHO), “Traditional medicine refers to health practices, approaches, knowledge and beliefs incorporating plant, animal and mineral based medicines, spiritual therapies, manual techniques and exercises, applied singularly or in combination to treat, diagnose and prevent illnesses or maintain well-being”1. Globally there is a resurgence of interest in traditional medicine and other non-conventional health care systems. Such systems include Chinese medicine, Ayurveda, Herbal medicine, Tibb Unani, Homeopathy, Acupuncture, Chiropractic, Osteopathy, bone-setting and many others. Variously named as Indigenous, folk, Traditional and Complementary Medicine (T&CM) and/or Complementary and Alternate Medicine (CAM), these systems of health care were until recently predominantly used by the poor and rural communities. They are however currently finding favor with the more educated and affluent communities of the developed world, and their use is rapidly expanding. The positive features of T&CM responsible for the rapid expansion of their use include diversity, flexibility, easy accessibility, relative low cost, low levels of technological input, relative low side effects and growing economic importance (WHO)5. Along with their affordability and accessibility these systems are firmly embedded in the belief systems of communities and are culturally compatible. Taking cognizance of the growing demand for and use of T&CM WHO developed guidelines and strategies for T&CM integration into conventional health care systems by member countries for the period 2002-2005 and recently 2014-2023. The 2014-2023 strategy has two key goals: to support Member States in harnessing the potential contribution of T&CM to health, wellness and people centered health care and to promote the safe and effective use of T&CM through the regulation of products, practices and practitioners. These goals will be reached by implementing three strategic objectives: 1) building the knowledge base and formulating national policies; 2) strengthening safety, quality and effectiveness through regulation; and, 3) promoting universal health coverage by integrating T&CM services and self-health care into national health systems1.